The Southwest Goiás: from Modernization of Agriculture to Agrobusiness (Revista LIDER, 2017)
The 1960s marks the process of agriculture modernization in the Southwest Region of the State of Goiás, Brazil, with the substitution of extensive grazing of beef cattle production for grain crops (rice, corn and soybeans) through the Technology Package. From the 1980s to the 1990s, the Industrialization of Agriculture became a reality, which intensified the relations between agricultural production and industrial plants that settled in the region. In the late 1990s and early twenty-first century, agribusiness consolidated itself with the installation of BRF (processor of poultry and pork) agro-industrial units. Natural conditions (soil, climate, topography, hydrography and pluviosity), land concentration, and public policies and financing, enabled the process of appropriation of space andspace elements from the Southwest Region. The research uses data of the agricultural demographic censuses from the Brazilian Institute of Geography and Statistics (IBGE) and the Mauro Borges Institute (IMB) to demonstrate that agribusiness is the current means of appropriation of agrarian and urban areas in the Southwest of Goiás by the financial and industrial capital